Pyrethroid-Degrading Microorganisms and Their Potential for the Bioremediation of Contaminated Soils: A Review - Cycoń, Mariusz; Piotrowska-Seget, Zofia (Frontiers in Microbiology, 2016)
Pyrethroid insecticides have been used to control pests in agriculture, forestry, horticulture, public health and for indoor home use for more than 20 years. Because pyrethroids were considered to be a safer alternative to organophosphate pesticides (OPs), their applications significantly increased when the use of OPs was banned or limited. Although pyrethroids have agricultural benefits, their widespread and continuous use is a major problem as they pollute the terrestrial and aquatic environments and affect non-target organisms. Since pyrethroids are not degraded immediately after application and because their residues are detected in soils, there is an urgent need to remediate pyrethroid-polluted environments. Various remediation technologies have been developed for this purpose; however, bioremediation, which involves bioaugmentation and/or biostimulation and is a cost-effective and eco-friendly approach, has emerged as the most advantageous method for cleaning-up pesticide-contaminated soils. This review presents an overview of the microorganisms that have been isolated from pyrethroid-polluted sites, characterized and applied for the degradation of pyrethroids in liquid and soil media. The paper is focused on the microbial degradation of the pyrethroids that have been most commonly used for many years such as allethrin, bifenthrin, cyfluthrin, cyhalothrin, cypermethrin, deltamethrin, fenpropathrin, fenvalerate and permethrin. Special attention is given to the bacterial strains from the genera Achromobacter, Acidomonas, Bacillus, Brevibacterium, Catellibacterium, Clostridium, Lysinibacillus, Micrococcus, Ochrobactrum, Pseudomonas, Serratia, Sphingobium, Streptomyces and the fungal strains from the genera Aspergillus, Candida, Cladosporium and Trichoderma, which are characterized by their ability to degrade various pyrethroids. Moreover, the current knowledge on the degradation pathways of pyrethroids, the enzymes that are involved in the cleavage of pesticide molecules, the factors/conditions that influence the survival of strains that are introduced into soil and the rate of the removal of pyrethroids are also discussed. This knowledge may be useful to optimize the environmental conditions of bioremediation and may be crucial for the effective removal of pyrethroids from polluted soils.